If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -3(-1x + 1) = -1x + -4 Reorder the terms: x + -3(1 + -1x) = -1x + -4 x + (1 * -3 + -1x * -3) = -1x + -4 x + (-3 + 3x) = -1x + -4 Reorder the terms: -3 + x + 3x = -1x + -4 Combine like terms: x + 3x = 4x -3 + 4x = -1x + -4 Reorder the terms: -3 + 4x = -4 + -1x Solving -3 + 4x = -4 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -3 + 4x + x = -4 + -1x + x Combine like terms: 4x + x = 5x -3 + 5x = -4 + -1x + x Combine like terms: -1x + x = 0 -3 + 5x = -4 + 0 -3 + 5x = -4 Add '3' to each side of the equation. -3 + 3 + 5x = -4 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = -4 + 3 5x = -4 + 3 Combine like terms: -4 + 3 = -1 5x = -1 Divide each side by '5'. x = -0.2 Simplifying x = -0.2
| f(x)=1+ln(1+ln(1+ln(1+x))) | | 19-(5m+7)=4+2m-13 | | 60(36)=60(k) | | (2b-1)i+(a+3)=4-8i | | 4t^2-20t-25=0 | | (3x-5)+(12x)=90 | | (3-2i)-(2x+yi)=7+6i | | 3a-10+4a=5a-7 | | 3.7b+7=8.1b-18.4 | | 42(z)=35(28) | | 4+3+-7=4+-7 | | 36(x)=45(32) | | (2x)=(2y-x) | | (3x-5)=(12x) | | C(x)=.6x+30 | | x-3(-x)+1=-x-6 | | 18(5)=7.5(x) | | 10-(3x-5)=11-4x | | 8+3x=132 | | 10x-50=7x-20 | | x-(3-x+1)=-x-6 | | X^2-11x+48=0 | | 11x-8=x | | 0=(-.02x^2)+1.7x+5.1 | | 90+2x-3+4x+11=180 | | 180=(180-(8x+10))+2x+10+x+30 | | X+6c=180 | | -2(-6-1)+3(-6+4)=8 | | (0.39-d)*(0.39-d)=0 | | 20=8+3(12-4x) | | 4x+11+2x-3=180 | | 8x+10=x+30 |